Analysis Of Parameters Assessment On Laminated Rubber-Metal Spring For Structural Vibration - Mohd Azli, Salim; Azma, Putra; Muhd Ridzuan, Mansor; Musthafah, Mohd Tahir; Mohd Zaid, Akop; Mohd Azman, Abdullah (IOP Publishing, 2016)
This paper presents the analysis of parameter assessment on laminated rubber-metal spring (LR-MS) for vibrating structure. Three parameters were selected for the assessment which are mass, Young’s modulus and radius. Natural rubber materials has been used to develop the LR-MS model. Three analyses were later conducted based on the selected parameters to the LR-MS performance which are natural frequency, location of the internal resonance frequency and transmissibility of internal resonance. Results of the analysis performed were plotted in frequency domain function graph. Transmissibility of laminated rubber-metal spring (LR-MS) is changed by changing the value of the parameter. This occurrence was referred to the theory from open literature then final conclusion has been make which are these parameters have a potential to give an effects and trends for LR-MS transmissibility.